Estimation of Rotation Gain Thresholds Considering FOV, Gender, and Distractors - Williams, Niall L.; Peck, Tabitha C. (IEEE transactions on visualization and computer graphics, 2019)
Redirected walking techniques enable users to naturally locomote in virtual environments (VEs) that are larger than the tracked space. Redirected walking imperceptibly transforms the VE around the user with predefined estimated threshold gains. Previously estimated gains were evaluated with a 40° field of view (FOV), and have not been evaluated in the presence of a distractor-a moving object in the VE that may capture the user's attention. We conducted a 2 (FOV: 40°, 110°) × 2 (Gender: female, male) × 2 (Distractor: without, with) user study to estimate and compare thresholds for rotation gains. Significant differences in detection thresholds were found between FOVs, and significant differences were found between female and male gains with a 110° FOV. Males had significantly wider gains using a 110° FOV compared to a 40° FOV, and distractors affected females differently than males. Finally, strong correlations were found between simulator sickness scores and threshold gains.